PENGARUH VARIABEL TRUST, PERCEIVED VALUE, BRAND ATTITUDE DAN CUSTOMER SATISFACTION TERHADAP CUSTOMER LOYALTY PELANGGAN MCDONALDS DRIVE THRU DI SURABAYA - Setiono, Lydia (Universitas Katolik Widya Mandala Surabaya, 2012)
Today, the competition is getting tougher in the services so as to encourage more companies to provide products and services that have high competitiveness. For the owner of a fast food restaurant services are increasingly recognizing their importance in order to achieve customer loyalty. The purpose of this study was to test the relationship between trust through brand attitude and customer satisfaction and perceived value through customer satisfaction of customer loyalty at McDonald's Drive Thru customers in Surabaya. The sampling technique in this study using purposive sampling method, so that the samples used in this study of 150 respondents. The data analysis techniques in this study used SEM (Structural Equation Modeling) and data processed using the program LISREL to analyze between trust through brand attitude and customer satisfaction and perceived value through customer satisfaction of customer loyalty. The results of this study reveal that trust have an influence onÂ customer loyalty through brand attitude and customer satisfactionÂ and showed a significant effect between customer loyalty through customer satisfactionÂ at McDonald's Drive Thru customers in Surabaya.